Cuticular hydrocarbon profiles of honey bees (Apis mellifera) change after parasitized by Nosema ceranae in hives treated with amitraz - Zufriategui, Camila (2023)
Cuticular hydrocarbons (CHC) are key-essential semiochemicals for honeybees with multiple functions, including the reduction of water loss and facilitation of intraspecific communication, such as recognition of nestmates. CHC patterns can be modified by genotype, physiological state, pathogens, and environmental context. Therefore, the present study aimed to characterize the CHC profile of Apis mellifera worker bees exposed to two stressors frequently found within the colony: Nosema ceranae - a prevalent fungal parasite- , and amitraz-an acaricide widely used for treating Varroa disease-. A semi-field assay was conducted using eight healthy hives, half of which were treated with amitraz strips (a drug commonly used to control mite disease). Three day-old-bees were individually marked on the thorax and introduced into the hives. Half of these introduced bees were infected with an inoculum of ca. 100000 N. ceranae spores. Consequently, four treatment groups were established: a) Control, b) Exposed to amitraz, c) Infected with N. ceranae spores, d) Infected with N. ceranae and exposed to amitraz. Afterwards, bees were sampled at two monitoring points (10 and 18-days post-emergence), and both parasitic load and CHC were quantified. When analyzing the evolution of the total CHC, it revealed a general reduction in the total mass for all treatments, except for the worker bees exposed to amitraz, whose values remained similar over time. However, focusing on the analysis of the 14 identified major CHC peaks, it was possible to recognize five hydrocarbons (nonacosane, ?-hentriacontene,?-hentriacontene, hentricontane, and tritriacontadiene) that exhibited a significant reduction in bees exposed to each one of the stress factors or their combination. Our results evidence a potential impact of chemical and biological stressors on in-hive communication cues. Whether these changes in chemical signaling are sufficient to be associated with alterations of social interactions is discussed.